Transformative Research Space Through Epistemic Indeterminacy of Mandala - Suresh Gautam (Journal of Education and Research, 2017)
The paper aims to explore how local epistemologies are emerged from the indeterminacy of the position and momentum of the researcher.  Using the symbol of Mandala, I depict such indeterminacy during the research process, which eventually fosters transformative research space.  I researched on urban youth of Kathmandu and their everyday life during 2012-2016.  During the research, I was engaged with some youth in Kathmandu for understanding their ways of being and living over there.  Despite being guided by particular epistemologies, I sought some local epistemologies from the narratives of my participants, which not only guided my research process but also demonstrated indefinite nature of reality. It helped me to understand the everyday life of urban youth in Kathmandu.  In so doing, here, I reflect the research process which interacts with other epistemic indeterminacy around Mandala.  Mandala in the Eastern (Hindu and Buddhist) tradition is known as a representation of a complex web of human life and activities, which portrays the mesocosm of everyday life of urban youth as integral part of time and space.